Acarbose With Comparable Glucose-Lowering but Superior Weight-Loss Efficacy to Dipeptidyl Peptidase-4 Inhibitors: A Systematic Review and Network Meta-Analysis of Randomized Controlled Trials - Zhang, Fang; Xu, Shishi; Tang, Lizhi; Pan, Xiaohui; Tong, Nanwei (Frontiers in Endocrinology, 2020)
Background: Acarbose and dipeptidyl peptidase-4 inhibitors (DPP-4is) have several similarities regarding their efficacy. Assessing the hypoglycemic and weight-loss effects as well as the tolerability between them at their optimal dosages, could provide a better management of adult type 2 diabetics. Methods: We perfomed a systematic review and network meta-analysis (NMA) on randomized controlled trials that were identified from the databases of EMBASE, MEDLINE, Cochrane Central Register of Controlled Trials, Web of Science, Conference Proceedings Citation Index, ClinicalTrials.gov, China National Knowledge Infrastructure, Wan Fang, and SinoMed. The trials with 300 mg/day of acarbose or the recommended doses of DPP-4is were the most optimal for our NMA. The mean differences (MD) and relative risk (RR) derived from eligible studies were used. Results: Among the 15411 obtained potential studies, 13 pair-wise trials and 48 monotherapy studies were included in the meta-analysis and NMA, respectively. DPP-4is had a greater at glucose-lowering effect, but a weaker at weight-loss effect than acarbose in pair-wise meta-analysis (p < 0.05). However, NMA with 11877 participants showed that, at their optimal doses, acarbose and DPP-4is had similar glucose-lowering effects on the 2-hour postprandial glucose (MD 0.96 mmol/L, 95% credible interval -0.56 to 2.54), HbA1c (0.05%, -0.25 to 0.33), and fasting plasma glucose reductions (-0.27 mmol/L, -0.76 to 0.24), and HbA1c < 7.0% target goal achievement (RR 1.33, 0.51-3.64). Acarbose was superior to DPP-4is regarding weight loss (MD -1.23 kg, -2.08 to -0.33). Acarbose had more withdrawal, gastrointestinal and overall adverse events than DPP-4is (p < 0.05), but the differences disappeared after longer treatment (p > 0.05). Conclusions: Acarbose and DPP-4is have similar glucose-lowering effects, but the weight-loss effects of acarbose are superior. Therefore, in the use of the most optimal dosages, overweight/obese type 2 diabetics might benefit more from a treatment with acarbose than DPP-4is.